2017
DOI: 10.3390/rs9090894
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of L-Band Brightness Temperature during Freeze/Thaw Events over a Prairie Environment

Abstract: Passive microwave measurements from space are known to be sensitive to the freeze/thaw (F/T) state of the land surface. These measurements are at a coarse spatial resolution (~15-50 km) and the spatial variability of the microwave emissions within a pixel can have important effects on the interpretation of the signal. An L-band ground-based microwave radiometer campaign was conducted in the Canadian Prairies during winter 2014-2015 to examine the spatial variability of surface emissions during frozen and thawe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The lower FT classification agreement over the northern (≥45 • N) domain may be attributed to a larger number of daily FT variations over the annual cycle and to wetter snow conditions during seasonal transitions [7,51], where the L-band snow volume emission becomes significant in the presence of even small amounts of snow liquid water [52]. However, the distribution of other physical landscape factors can degrade the Tb signal-to-noise and influence the associated FT accuracy pattern [51,53].…”
Section: Ft Classification Assessmentmentioning
confidence: 99%
“…The lower FT classification agreement over the northern (≥45 • N) domain may be attributed to a larger number of daily FT variations over the annual cycle and to wetter snow conditions during seasonal transitions [7,51], where the L-band snow volume emission becomes significant in the presence of even small amounts of snow liquid water [52]. However, the distribution of other physical landscape factors can degrade the Tb signal-to-noise and influence the associated FT accuracy pattern [51,53].…”
Section: Ft Classification Assessmentmentioning
confidence: 99%
“…The FT-AP is archived and distributed by the NASA Distributed Active Archive Center of the National Snow and Ice Data Center (NSIDC DAAC). The FT-AP can be accessed through the NSIDC online public data server (https: //nsidc.org/data/aq3_ft/versions/5, Roy et al, 2018). Table 6 summarizes all the datasets used in this study and lists where they are available for download.…”
Section: Data Availabilitymentioning
confidence: 99%
“…This study presents the new Aquarius passive FT product for the Northern Hemisphere (Roy et al, 2018), distributed by the US National Snow and Ice Data Center (NSIDC) at http://nsidc.org/data/nsidc-0736/versions/1. The product precision and uncertainties are addressed by comparing Aquarius FT retrievals with the FT-ESDR product for the overlapping period (2011-2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the large antenna full beamwidth (30 • ) and the footprint geometry of the surface-based radiometer, the simulated T B of a single directional incidence angle (θ) might not be representative of the measured T B over a large footprint, especially at higher incidence angles [37]. Hence, in this study, a weighting function was computed to estimate the integrated T B within the footprint for a range of incidence angles.…”
Section: Footprint Integrationmentioning
confidence: 99%
“…Roy et al [37] showed that spatially distributed surface-based radiometer observations within a SMOS pixel gives constantly lower T B (between 8.5 and 22.9 K) than SMOS observations at 60 • V-pol (not apparent at lower incidence angles). It was hypothesized that these discrepancies were due to the large beamwidth (30 • ) of the surface-based radiometer, which produced an incidence angle in the far range of up to 75 • .…”
Section: Footprint Integrationmentioning
confidence: 99%